Incidence of urogenital neoplasms in India - Satyanarayana Labani; Dishank Rawat; Smita Asthana (Indian Journal of Medical and Paediatric Oncology)
Objective: To study and compare the national and regional incidences and risk of developing of neoplasms of individual urogenital sites using 2012 – 2014 reports from the National Cancer Registry Programme (NCRP) data. Materials and Methods: A number of incident cases, age-adjusted rates (AARs), and cumulative risk (0 – 64 years) pertaining to urogenital neoplasms, along with the ICD-10 codes, were extracted. Data on indicators, namely number of incident cases, AARs and one in a number of persons develop cancer were summarized for both the sexes in each of the cancer registries and presented region-wise in the form of ranges. Results: The proportion of all urogenital neoplasms in comparison to all cancers was 12.51% in women and 5.93% in men. Risk of development of urogenital cancers for women was maximum (1 in 50) in the North-eastern region, followed by Rural West, South, and North. For men, the risk of developing neoplasms of urogenital sites was highest (1 in 250). For the neoplasms of the renal pelvis and ureter, both the incidence and risk were quite low for all genders across all the regions. Cervical neoplasms had the highest incidence (4.91 – 23.07) among female genital neoplasms, while prostate had the highest incidence (0.82 – 12.39) among male genital neoplasms. Conclusion: Making people aware of urogenital neoplasms and their risk factors are important for the public health awareness point of view. Centers that deal with either management of urogenital cases or/and screening of genital neoplasms could serve as the designated centers for creating such awareness.